Pendampingan Pengeringan Tanaman Obat dengan Tipe Fluidized Bed Dryer untuk Usaha Mikro, Kecil dan Menengah di Kota Bogor - Umi Cahyaningsih; Tjahja Muhandri; Arifin Nugraha (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Drying with the fluidized bed dryer type is a drying process by blowing hot air from the bottom onto a stretch of material, so that the material scatters to resemble fluid properties. The drying method with dry air is used to speed up the drying process and maintain the quality of the dry ingredients. The purpose of this service is to provide theoretical and practical drying training to the micro, small and medium enterprises (MSME) group so that they are able to produce dry materials of good quality, namely green color and low water content so they are not easily damaged and can last longer. The assistance was carried out for Naphyco MSME partners and representatives of RW 10 residents, Tanah Baru Village, North Bogor District, Bogor City in October 2022 at Naphyco MSME partner locations. The training was carried out using two methods, namely presentation and hands-on practice of drying medicinal plants with a fluidized bed dryer. The positive impact of this assistance is to gain knowledge about how to dry medicinal plants faster than drying them in direct sunlight, and also to obtain leaves of medicinal plants that are green in color (not brown). The achievement of mentoring activities can be seen from the results of the pre-test and post-test. The results of the questionnaire showed an increase in participant knowledge from a good score of 55.6% to 88.9%, a moderate score from 22.2% to 0% and a value less than 22.2% to 11.1%. There was also an increase in participants' interest in the questionnaire statements who strongly agreed from 66.7 to 88.9%, who agreed from 33.3% to 11.1%. The results of the questionnaire above need to be continued with a mentoring program for other MSME members to produce quality products as raw materials.